Growth parameters of trickle fertigated potato (Solanum tuberosum) - CRAWLA, J K; NARDA, N K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994-96 on potato (Solanum tuberosum L.) to determine the impact of does of urea, frequency of fertigation and wetted soil volume using trickle fertigation on various plant growth parameters for potato crop and compared with the conventionally grown crop. Results revealed that leaf area index, per cent ground cover and dry-matter accumulation were higher in the trickle fertigated crop than the furrow irrigated but conventionally fertilized crop while the plant height was more in the later. The maximum fresh tuber yield ws 36.29 tonnes/ha with an average of 30.13 tonnes/ha in the trickle fertigated crop as compared to 21.5 tonnes/ha for the furrow-irrigated crop.